EFFECTIVENESS OF LIFE INSURANCE CLAIM DISPUTE RESOLUTION PROCEDURES THROUGH THE CONSUMER DISPUTE RESOLUTION AGENCY (BPSK) - Faradiba Aulia Rahmah; Padian Adi Salamat Siregar (Inspiring Law Journal, 2025)
The effectiveness of life insurance claim dispute resolution procedures through the Consumer Dispute Resolution Agency (hereinafter abbreviated as BPSK) is an important aspect in efforts to protect insurance service consumers legally. Life insurance claim disputes often arise due to claim rejection by insurance companies, differences in interpretation of policy content, and default in the implementation of insurance agreements. This study, BPSK plays a role as a non-litigation institution that provides alternative dispute resolution that is faster, simpler, and less expensive than court channels, however, the effectiveness of the implementation of dispute resolution procedures through BPSK remains a problem, due to resource constraints or a lack of public understanding of the functions and authorities of BPSK, limited competent human resources in the insurance sector, overlapping authorities with other institutions such as the OJK and the courts, and weak implementation of BPSK decisions in the field.The research method used is a normative juridical approach by examining applicable laws and regulations, legal doctrine, and relevant literature related to consumer protection and insurance law. This research is descriptive-analytical, with data collection through a literature study focusing on the provisions of Law Number 8 of 1999 concerning Consumer Protection, Law Number 40 of 2014 concerning Insurance, and other implementing regulations. The research analysis focuses on the extent to which dispute resolution procedures at the BPSK are able to guarantee effective legal protection for consumers, particularly in life insurance claim disputes.The research results show that the BPSK plays a strategic role in resolving life insurance claim disputes, but its effectiveness is not optimal. The main obstacles include limited competent human resources in the insurance sector, low public understanding of the BPSK's functions and authorities, overlapping authority with other institutions, and weak implementation of BPSK decisions. Efforts to increase the effectiveness of dispute resolution require strengthening the BPSK institution, improving coordination between institutions, increasing insurance company compliance, and enhancing consumer literacy so that legal protection can be more optimally realized.